Profile likelihood estimation of partially linear panel data models with fixed effects - SU, Liangjun (Institutional Knowledge at Singapore Management University, 2006)
We consider consistent estimation of partially linear panel data models with fixed effects. We propose profile-likelihood-based estimators for both the parametric and nonparametric components in the models and establish convergence rates and asymptotic normality for both estimators.